Listeners perceive prefixes differently: Evidence from a noise-rating task. (April 2015) - Pycha, Anne
Abstract : When compared to suffixes, prefixes possess several distinctive but largely unexplained properties. This paper explores the idea that these properties might arise from a common source, namely discontinuous recognition of spoken prefixed words, in which listeners 'skip' to that portion of the speech stream which contains the root. If this occurs, listeners could potentially perceive prefixes very differently than roots and suffixes. We investigated this idea with a noise-rating task, which measures the extent to which noise subjectively interferes with speech. Using newly-coined derived English words as a stimuli, participants rated the loudness of white noise overlaid on portions of spoken words corresponding to prefixes, word-initial roots, or suffixes. Results indicate that participants gave overall higher loudness ratings to noise on prefixes compared to noise on suffixes. Furthermore, as signal-to-noise ratios decreased, participants increased their loudness ratings at greater rates for noise on roots compared to noise on prefixes. These results support the discontinuous hypothesis, and suggest that prefixed words introduce a perceptual bias which could explain the development of certain distinctive prefix characteristics over time.